2011
DOI: 10.5539/ass.v7n9p33
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Implementation Level of the Total Quality Management Principles by the Principals and Teachers Functioning at Elementary Schools: The Case of Adiyaman Province

Abstract: This study is conducted for the purpose of examining the implementation levels of the Total Quality Management principles by the principals and teachers functioning at the elementary schools. The study is executed with 30 school principal and 300 teachers functioning at the public elementary schools in Adıyaman province. A questionnaire set up by the researchers after consulting to the expert opinion is used for data gathering. Data concerning the study is analyzed by using SPSS package software. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Figure2: PLS-Path Modeling Graph Some items or variables have measurements of less than 0.5 that were removed because it is considered to be of low level of reliability [23].…”
Section: Results By Measurement Modelmentioning
confidence: 99%
“…Figure2: PLS-Path Modeling Graph Some items or variables have measurements of less than 0.5 that were removed because it is considered to be of low level of reliability [23].…”
Section: Results By Measurement Modelmentioning
confidence: 99%
“…TQM in education contributes significantly to principals, teachers, students, and other school stakeholders to know each other's roles and to produce customer satisfaction. In other words, TQM paved the way for producing student-oriented insights (Donlagic & Fazluc, 2015;Taşar & Çelik, 2011). Also, according to Batra, Shankar, and Kumar (2012), TQM has a direct influence on an individual enhancement that can foster more significant commitment and team spirit in managing organizations.…”
Section: The Importance Of Tqm In Educationmentioning
confidence: 99%
“…Mubaraki (2013) showed, in general, the application of TQM principles varies between medium to high rate and the Inferential Statistics results showed a two principals have significant statistically relationship which are focus on customer and continuous improvement. Tasar at al (2011) in the research of "Examination of Implementation Level of the Total Quality Management Principles by the Principals and Teachers Functioning at Elementary Schools" it was observed that the principals and teachers functioning at the elementary schools implement the Total Quality Management principles at their occupational studies. It is further determined that the teachers have higher implementation levels than the principals as regards such principles.…”
Section: Review Of Literaturementioning
confidence: 99%